PORTUGUESE DRAMA AND THE DIALECT OF ENLIGHTENMENT: THE MYTH OF PROMETHEUS IN “OS DEGRAUS” BY AUGUSTO SOBRAL / O TEATRO PORTUGUÊS E A DIALÉTICA DO ESCLARECIMENTO: O MITO DE PROMETEU EM OS DEGRAUS, DE AUGUSTO SOBRAL - Silva, Agnaldo Rodrigues da; Oliveira, Adilson Vagner de (Revista ECOS, 2016)
This paper presents a discussion on the resignification of the myth of Prometheus, in order to articulate a study of the play Os Degraus (1964), by the Portuguese playwright Augusto Sobral. In this direction, we aim to focus on the Portuguese scenic production of the 1960’s, as well as the path of this myth over the centuries, from the vision built on the metaphor of fire that, mythologically, saved the world from darkness, an artifice to represent the human ignorance in a particular period of human history. A meaningful play of the modern Portuguese drama, Os Degraus is a scenic text which reaffirmed the commitment of Sobral to substantial analysis of society in times of political crisis, leading to the stage new philosophical and sociological projects.